Fatigue as hallmark of Fabry disease: role of bioenergetic alterations - Gambardella, Jessica; Riccio, Eleonora; Bianco, Antonio; Fiordelisi, Antonella; Cerasuolo, Federica Andrea; Buonaiuto, Antonietta; Di Risi, Teodolinda; Viti, Alessandro; Avvisato, Roberta; Pisani, Antonio; Sorriento, Daniela; Iaccarino, Guido (Frontiers in Cardiovascular Medicine, 2024)
Fabry disease (FD) is a lysosomal storage disorder due to the impaired activity of the α-galactosidase A (GLA) enzyme which induces Gb3 deposition and multiorgan dysfunction. Exercise intolerance and fatigue are frequent and early findings in FD patients, representing a self-standing clinical phenotype with a significant impact on the patient's quality of life. Several determinants can trigger fatigability in Fabry patients, including psychological factors, cardiopulmonary dysfunctions, and primary alterations of skeletal muscle. The "metabolic hypothesis" to explain skeletal muscle symptoms and fatigability in Fabry patients is growing acknowledged. In this report, we will focus on the primary alterations of the motor system emphasizing the role of skeletal muscle metabolic disarrangement in determining the altered exercise tolerance in Fabry patients. We will discuss the most recent findings about the metabolic profile associated with Fabry disease offering new insights for diagnosis, management, and therapy.